ANALISIS AKUNTABILITAS, TRANSPARANSI, DAN PRINSIP KONSISTENSI PADA LAPORAN KEUANGAN ENTITAS NONLABA BERDASARKAN ISAK 35 - Aditya, Maulana (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to assess the extent to which the financial reports of Al-Arqam Mosque comply with ISAK 35 by measuring accountability, transparency, and the concept of full disclosure. In-depth interviews, document analysis, and observation were all used in this qualitative case study. The study's conclusions indicate that, despite challenges such as lack of human resources and lack of knowledge of accounting principles, financial reporting remains easy to understand. Accountability is reduced due to the absence of a monitoring system, transparency is reduced due to the absence of a legislative framework requiring transparency and independent audits, and the concept of consistency has not been implemented. According to these findings, ISAK 35 should be widely used to promote more accountable and transparent financial management in mosques and to fully achieve the idea of ​​transparency.